DINAMIKA EKSPRESI EMOSI MELALUI GARIS DAN WARNA - Aldi Yunaldi (Besaung : Jurnal Seni Desain dan Budaya, 2016)
Essentially art of painting can’t be separated from lines and colors. Lines are the basic element in fine art that means more than just a scrapes. Even the lines with the rhythm could raises an impression on the observer. In this masterpiece dynamics of expression of emotions through the line and color with music as copyright stimulation is main theme which presented. Role of the line is very important in the process of forms embodiment  to determining the quality of an artist's expression. Expression was seen in sweep or giving certain accentuation on the creation object. When the line be given structured, for example, organized through the rhythm, symmetric, equilibrium, would form a patterns certain so that the line can speak as a expression media. Concepts it was underlying the creation of this work are realized form Expressionism Abstract with the concept approach through the personal expression that interaction communication between five senses and the relationship feeling and mind. In this case the line have imaginary impression on observers, the line very fundamental to presenting expression in a work of art of painting. The reality of life in the environment inspiring in who working transferred to the two-dimensional plane through the line scrapes and color. The mastery of the properties correspond line with the rhythm likely straight line giving a different feeling with curved line, straight line giving a curved stiffness and flexible impression , also gentleness impression. As well as the color, the general meaning of the color actually was described. With notes if the colors are in a state of standself or be dominant than another colors. These paintings hopefully can be motivational for other artists in making the work.Keywords : Expression, Emotion, line, colour, music.